Топоніми Бистрик, Білокопитове, Шалигине, Яструбщина виникли у арабо-візантійський час - Тищенко, К.М. (Сіверщина в історії України, 2020)
Помічено зв’язок групи топонімів Жаб’є з ім’ям м. Jābiya Джабія, столиці гасанідів (арабів-християн і федератів Візантії у VI ст.). Це сприяє розумінню того, чим були історично пов’язані усі досі відомі репліки в Україні від прототипів з Палестини й Сирії візантійського часу, – починаючи з зауважених іще у XIX ст. Трипілля й Халеп’я. У такому разі топооснови Копит-, Бистр-, Яструб- і Шалиг- мають бути репліками сирійської назви м. Джабії – Ґабіта, імен нп Бустра у Палестині і Ясріб (тепер Медіна) в Аравії та геноніма салихидів – федератів Візантії у V ст. Наявні у цих же контекстах топооснови, схожі на імена реалій ісламу, постають тепер не як синхронний, а як хронологічно наступний пласт виявленого цілого, даючи нове уявлення про складність історичного процесу у Наддніпрянщині у переламні післячерняхівські часи IV–VIII ст. A group of Zhabye toponyms in Ukraine is akin with the name of Jābiya, the capital of Hassanids, the Christian Arabs federates of Byzantium. The history of this period was investigated, in particular, by N. Pigulevskaya and I. Shahid. The first Arab federates of Byzantium were Tanukhids (4th century), then Salihids (5th century) and Hassanids (6th century). It is known that until the 8th century they were zealous Christians, venerated the Apostle Thomas and St. Sergius, whose shrine was in Syria (Rosafa-Sergiopolis). A trace of the historical presence of all three tribes is now found in the toponymy of Ukraine (Taniushivka, Stanyshivka (2); Salykha (3), Solyhy; Hasanivka, Khasanivka (2) etc.). In the vicinity of each object with such names, an accompanying context was found from synchoric and synchronous toponyms-replicas of Syrian prototypes (Rosava, Serhii, Polohy, Poloshky, Murafa, Muraveinia, Ivot etc.). This indicates the continued presence of Christian Arabs in the Middle Dnieper Area for three centuries. The arguments set forth refute the traditional thesis that direct contacts with Arabs were impossible, because Arabs were supposedly always separated from the Dnieper Area by Christian Byzantium. It turns out now that for three centuries the Arabs themselves were part of Byzantium. This recently discovered contacts contribute to the re-evaluating of the whole problem. It was this period (IV–VI centuries) that could be the main time for the formation of that significant stratum of toponymical replicas in Ukraine from prototypes of Syria and Palestine, the first place names of which were noticed back in the 19th century (Trypillia, Halep: V. Zavitnevych, A. Sobolevs’kyj). As a result of a new targeted search, numerous replicas of the genonyms of Tanukhids, Salihids and Hassanids were also found in the toponymy of neighboring lands – from the Czech Republic, Poland and Sorabs hence the regions of Russia on the upper West Dvina, Dnieper and Volga. In the light of the search, the Kopyt-, Bystr-, Yastrub- and Shalyh- stems of some Severian Area toponyms can, in particular, be replicas of the Syrian name of Jābiya – Gabita, the place names of Bustra in Palestine, Yathrib (Medina) in Arabia, and the genonym of the Salihids, Byzantine federates of the 5th c. The realities of Islam present almost in all these contexts appear now not as synchronic, but as a chronologically subsequent layer of the revealed whole. It opens up a new vision of the complicated historical process in the Middle Dnieper Area in the IV-VIII centuries, the crucial time which followed here the period of the archeological culture of Cherniakhov-Sîntana de Mureş.